Curcumin attenuates AFB1-induced oxidative stress and pyroptosis-associated responses while improving autophagy-related signaling in HD11 macrophages - Shenao Wang; Chongren Zhong; Xiaoxuan Zong; Jiawei Ma; Ruoshi Zhang; Xingjun Feng (Toxicon, 2026)

Single-site amino acid residue mutation reshapes the characteristics of double bond positions for protostadienol-type triterpenols - Pengyang Lin; Yunpeng Wang; Bing Li; Xuebingting Zhang; Baolian Fan; Ruoshi Huang; Zhongju Ji; Fan Zhang; Jingcai Liang; Lixin Duan (Phytochemistry, 2026)

An extracellular miRNA reshapes cell wall integrity to prime systemic immunity in tomato - Yue Qiao; Yu Xia; Jianfei Shi; Zihan Song; Liying Jin; Lijie Xuan; Haolin Yang; Xiang Yu; Ruoshi Wang; Haiyan Liu; Ali Zhang; Jinfeng Chen; et al. (Molecular Plant, 2026)

Biogeochemical dynamics of dissolved organic matter in the Changjiang Estuary during a late flooding season - Zhongqiao Li; Ruoshi Zhao; Xiao Ma; Xiaona Wang; Liang Su; Hongliang Li; Haiyan Jin; Jiangning Zeng; Jianfang Chen (Frontiers in Marine Science, 2025)
To address the knowledge gap concerning the behavioral dynamics of dissolved organic matter (DOM) in the Changjiang Estuary during the late flooding season, we conducted an extensive sampling campaign during which 188 water samples were systematically collected across the estuary from August 15th to September 4th, 2021. Through analysis of dissolved organic carbon (DOC) concentrations and optical properties, this study aimed to elucidate the spatial distribution patterns and biogeochemical transformations of DOM during estuarine mixing processes in the late flooding season of the Changjiang. DOC in our study ranged from 0.72 to 2.24 mg/L, with a mean (± standard deviation) of 1.15 ± 0.32 mg/L. The correlation with salinity clearly indicated the dual control of hydrodynamic mixing processes and localized organic matter inputs on DOM abundance. Spectroscopic characterization combined with PARAFAC modeling revealed the predominantly terrestrial signature of chromophoric DOM (CDOM) and its progressive transformation along the estuarine gradient. Notably, rapid consumption of protein-like fluorescent DOM (FDOM) was observed within the Changjiang Estuary’s low-salinity transition zone. The consistent decrease in DOM aromaticity (SUVA 254 decline of 0.13 L·mg C -1 ·m -1 per salinity unit, r 2 = 0.77) coupled with increasing spectral slope S 275-295 (an increase of 0.0006 nm -1 per salinity unit) clearly demonstrates selective removal of terrestrial constituents, and molecular weight reduction through estuarine processing. These results demonstrate that photochemical degradation might dominate CDOM removal in the Changjiang Estuary.

Enhanced biosynthesis of 6-aminocaproic acid in engineered Escherichia coli with artificial protein cage-organized enzymatic cascades - Ruoshi Luo; Lin Hu; Dan Wang; Kaixing Xiao; Xuemei Liu; Yaqi Kang; Qinhong Wang (Bioresource Technology, 2025)

Mineralization preparation of PVDF@TA/MnO2 nanofiber membrane for efficient oil-water separation and dye degradation - Ruoshi Zhang; Jiuyun Cui; Hailong Wang; Qihang Liu; Can Wei; Jirong Luo; Atian Xie (Journal of Environmental Chemical Engineering, 2025)

Winter Dormant Wheat Will Benefit From Mean Temperature Increase of 2°C When Well‐Watered and Fertilized in the Main Producing Regions of China - Ruoshi Wang; Chuang Zhao; Senthold Asseng; Bing Liu; Alex C. Ruane; Jiahui Cong; Xi Wang; Zhijuan Liu; Jin Zhao; Xiaoguang Yang (Global Change Biology, 2025)
Rising temperatures are projected to lead to a decline in global wheat production. However, this global trend belies the regional nuances of this impact, such as observed local yield increases in some field experiments in the winter wheat‐growing region of China. This study combines detailed data from eight field warming experiments and outputs of simulation by an ensemble of three point‐based crop models and an ensemble of 10 global gridded crop models to scrutinize the influence of warming on winter wheat yield in the main producing regions of China (MPC). Observed data were obtained from published reports of field experiments, where winter wheat was grown with sufficient water and nitrogen under free‐air‐temperature increase (FATI) by 2°C. Growth and physiology of winter wheat in the field experiments were simulated by three point‐based crop models to validate the effects of warming on wheat growth and yield as simulated by grid‐based crop models. Results of field observations and grid simulations both indicate notable increases in average grain yield (observed +13%, simulated +8%) and aboveground biomass (observed +15%, simulated +7%) under 2°C warming across the MPC. The winter dormancy and pre‐anthesis duration were shorter with warmer temperature, with the effect that the grain filling period between anthesis to maturity was extended by 6 days. The shorter phenology affected wheat photosynthesis because less solar radiation was available (−6%) over the growth period. However, the leaf area index started to develop earlier and reached a higher maximum than un‐warmed control, so the cumulative solar radiation for photosynthesis intercepted by warmed wheat was higher (+9%), as well as the radiation use efficiency (+1%). These findings suggest that well‐irrigated and well‐fertilized winter dormant wheat is likely to experience yield gains with local warming of up to 2°C, bolstering confidence in future adaptation of wheat production in China.

Quality of chicken breast meat improved by dietary pterostilbene referring to up-regulated antioxidant capacity and enhanced protein structure - Yingjie Wang; Xin Zhou; Mengru Liu; Haoran Zang; Ruoshi Zhang; Hao Yang; Sanjun Jin; Xueyan Qi; Anshan Shan; Xingjun Feng (Food Chemistry, 2023)

Association of Sandstone-Type Uranium Mineralization in the Northern China with Tectonic Movements and Hydrocarbons - Yin Chen; Peisen Miao; Jianguo Li; Ruoshi Jin; Hualei Zhao; Lulu Chen; Cong Wang; Haoyu Yu; Xiaoru Zhang (Journal of Earth Science, 2022)

East Asian Summer Monsoon moisture sustains summer relative humidity in the southwestern Gobi Desert, China: evidence from δ18O of tree rings - Qiang Li; Yu Liu; Takeshi Nakatsuka; Keyan Fang; Huiming Song; Ruoshi Liu; Changfeng Sun; Gang Li; Ke Wang (Climate Dynamics, 2019)

Covalently mucoadhesive amphiphilic prodrug of 5-fluorouracil for enhanced permeation and improved oral absorption - Yan Liu; Dongyang Zhao; Mengchi Sun; Wei Wei; Yingli Wang; Jiahua Zhou; Ruoshi Zhang; Jian Wang; Haotian Zhang; Zhonggui He; Qiming Kan; Jin Sun (Drug Delivery and Translational Research, 2018)

Tree‐ring‐based precipitation reconstruction in the source region of Weihe River, northwest China since AD 1810 - Changfeng Sun; Yu Liu; Huiming Song; Ruochen Mei; Paramate Payomrat; Lu Wang; Ruoshi Liu (International Journal of Climatology, 2018)
A tree‐ring width chronology of Picea purpurea Mast from Mt. Shouyang in the source region of Weihe River (SWR), northwest China, was developed in this study. Correlation analysis showed that the precipitation from previous August to current July was the limiting climate factor of tree growth. Using a reliable and stable linear regression model, which explained 42.6% of the variance of the actual precipitation during the calibration period from 1958 to 2014, a 205‐year long precipitation series was reconstructed for the SWR. The dry years in the reconstruction were well supported by historical documents, and famous historical droughts were also recorded in the dry periods of a low‐frequency scale of the reconstructed precipitation. As demonstrated by the spatial correlation patterns, the reconstructed series compared well with other hydroclimate records for northwest China, indicating that it could represent large‐scale hydroclimate changes. The 2–8‐year interannual cycles and the interdecadal quasiperiods of 15.9 years and 18.6 years revealed that the precipitation in this region was probably affected by the El Niño‐Southern Oscillation and North Atlantic Oscillation. The dry/wet years corresponded well with the El Niño/La Niña events and the SWR commonly experienced droughts during the low periods of North Atlantic Oscillation.

Decoding early myelopoiesis from dynamics of core endogenous network - Hang Su; Gaowei Wang; Ruoshi Yuan; Junqiang Wang; Ying Tang; Ping Ao; Xiaomei Zhu (Science China Life Sciences, 2017)